The use of Virtual Reality for upper limb rehabilitation of hemiparetic Stroke patients - Antonio Vinicius Soares; Simone Suzuki Woellner; Camile dos Santos Andrade; Thiago Julian Mesadri; Alessandro Diogo Bruckheimer; Marcelo da Silva Hounsell
Introduction The Stroke is a neurologic disturbs that leads to a serious impact to the functionality and the quality of life of the survivors. It is necessary to develop new tools with rehabilitation objectives, where the Virtual Reality (VR) is introduced as a useful therapeutic resource to the motor recovery, in an attractive and efficient way, restoring functions through adapted games. Objective Analyzing the therapeutic effects of the Virtual Reality (Serious Game) in the recovery of the upper limb in hemiparetic Stroke patients. Methods Quasi-experimental research type time series, there are three pre and three post-tests already accomplished around 20 VR sessions. In the assessments the following measurement instruments were used: Fugl-Meyer Scale - session of the upper limb (FMS - UL); Range of Motion (ROM) for flexion and abduction shoulder; Box and Block Test (BBT); Nine Holes and Peg Test (9HPT); the Nottingham Health Profile (NHP); and the Modified Ashworth Scale (MAS). Results Significant gains were observed in the FMS-UL tests, with increase of 25.6%; increase ROM of shoulder with 34.0% for abduction and 19% for flexion; BBT 25.0%; also reported improvement in quality of life by NHP; it did not occurred significant alterations for 9HPT nor in MAS. Conclusion Although the results found in this research are preliminary, they are indicative that the VR can contribute for the recovery of the upper limb in hemiparetic Stroke patients.